2015
DOI: 10.4049/jimmunol.1401195
|View full text |Cite
|
Sign up to set email alerts
|

IgM-Dependent Phagocytosis in Microglia Is Mediated by Complement Receptor 3, Not Fcα/μ Receptor

Abstract: Microglia play an important role in receptor-mediated phagocytosis in the CNS. In brain abscess and other CNS infections, invading bacteria undergo opsonization with immunoglobulins (Ig) or complement. Microglia recognize these opsonized pathogens by Fc or complement receptors triggering phagocytosis. Here we investigated the role of Fcα/μ receptor (Fcα/μR), the less studied receptor for IgM and IgA, in microglial phagocytosis. We showed that primary microglia, as well as N9 microglial cells, express Fcα/μR. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 59 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…GAP43 is important for the glutamate uptake activity in reactive astrocytes following LPS challenge [109] or ischemic conditions [21,69,107]. Additionally, TLR3 expression in astrocytes appears to be critical to the astrocytic response to IPC [110]. Thus, many of the molecular pathways implicated in LPS studies of astrocytic activation and response may overlap with findings in IPC-mediated astrocytic activation.…”
Section: Astrocytesmentioning
confidence: 99%
“…GAP43 is important for the glutamate uptake activity in reactive astrocytes following LPS challenge [109] or ischemic conditions [21,69,107]. Additionally, TLR3 expression in astrocytes appears to be critical to the astrocytic response to IPC [110]. Thus, many of the molecular pathways implicated in LPS studies of astrocytic activation and response may overlap with findings in IPC-mediated astrocytic activation.…”
Section: Astrocytesmentioning
confidence: 99%
“…While this function was initially attributed to Fca/mR, it was recently shown that any phagocytosis may result as an extension of the complement cascade (via the opsonin C3 and complement receptor 3 on phagocytes). 21,99 Excluding the IgG class, IgM has the most extensive history of clinical use. One IgM antibody, nebacumab, was approved by several European countries in the early 1990s for the treatment of gram-negative sepsis, but it was subsequently withdrawn because of a variety of factors including high toxicity, high cost, and an inability to diagnose which cases of sepsis would be suitable for nebacumab use.…”
Section: Immunoglobulin Mmentioning
confidence: 99%
“…The complement system regulates the activation of mononuclear phagocytes. The binding of C1q or cleavage products of C3 with the complement receptors on mononuclear phagocytes produce inflammatory cytokines [126,127], and promote phagocytosis of pathogens or apoptotic cells [128][129][130][131].…”
Section: Inflammation Versus Resolutionmentioning
confidence: 99%